Adoptive gay fathers' sensitivity and child attachment and behavior problems. Issue 3 (3rd May 2020) - Feugé, Éric Alain; Cyr, Chantal; Cossette, Louise; Julien, Danielle
ABSTRACT: Fathers' sensitivity and child attachment security and externalizing and internalizing problems were investigated among families headed by two adoptive gay fathers. A sample of 68 fathers and their 34 children aged 1–6 years participated in the study. Fathers completed a sociodemographic questionnaire and the Child Behavior Checklist. Parental sensitivity and child attachment security were assessed by independent coders with Q-sort methodology during parent–child interactions at home. Results indicate that few children had low attachment security scores and behavior problems in the clinical range. Fathers' sensitivity within parenting couples appeared similarly high, as did children's attachment security. In contrast to the weak association found in past studies among heterosexual fathers, a significant moderate correlation was found between paternal sensitivity and child attachment security. Also, children with higher levels of attachment security had less externalizing problems.